Variabilidade espacial do estado nutricional do cafeeiro canephora visando o manejo localizado - de Oliveira, Rone Batista [UNESP]; Lima, Julião Soares de Souza; Silva, Samuel de Assis; Antuniassi, Ulisses Rocha [UNESP]; da Silva, Alessandra Fagioli [UNESP] (My University, 2010)
Mapping the plant nutritional condition allows viewing different regions in a cropping area, providing the producers with different criteria to use foliar and soil fertilization. The aim of this study was to evaluate the spatial variability of the nutritional condition of canephora coffee (Coffea canephora Pierre ex Froehner) regarding the site specific management of foliar and soil fertilization. In a one hectare area 60 georeferenced points were sampled at irregular intervals. There were five plants in each sampled point; two pairs of leaves were removed from the lateral branches (3 rd and 4 th pairs from extremity to the basis) in the cardinal points of each plant, counting up 40 leaves per point. The foliar samples were chemically analyzed for the following nutrients: N, P, K, Ca, Mg, S, B, Cu and Zn. The same pattern of spatial dependence was presented with adjustment for K and B. Except for N and P, which presented random distribution, the other nutrients presented mild to severe spatial dependence justifying the geostatistical data analysis for making maps for differential and located, foliar and soil fertilizer application in coffee crop.
Spatial variability of the nutritional condition of canephora coffee aiming specific management
Keywords: Leaf nutrition; Precision agriculture; Variograms; Coffea canephora